Estratégias discursivas do ex-presidente Jair Bolsonaro no Twitter/X durante o enfrentamento à pandemia da Covid-19 entre 2020 e 2022 no Brasil - Souza, Kennedy Anderson Cupertino de (2024)
The research aims to analyze the discursive strategy of former President Jair Messias Bolsonaro during the Covid-19 pandemic in Brazil. The Digital Discourse Analysis (DDA) is used as the theoretical and methodological foundation. With the support of data collection and analysis software, the corpus was explored to account for the multiplicity of information on the Twitter platform. The posts from the personal profile @jairbolsonaro, a social and political actor with significant influence nationally and internationally, utilize digital communication as a power relationship, and the interactions of digital network users formed the research corpus, covering the pandemic period from January 2020 to June 2022, organized into five phases. The analyses reveal strategies aimed at transforming versions into facts. The theoretical studies encompass the fields of discourse, digital discourse analysis, communication, and digital social networks.